A History of Japanese Literature, Volume 2 : The Early Middle Ages - Konishi, Jin'ichi, 1915-2007 (Princeton legacy library., 2018)
The second of live volumes planned to give a systematic account of Japanese literature from its beginnings to the death of the modern novelist Mishima, this book establishes the character of the literature of the early Middle Ages, from the ninth to the mid-twelfth century.